(untitled) (Educação e Pesquisa, 2022)
This study evaluates the traditional entrance exam in high education institutions in Brazil, the vestibular, as opposed to the use of the National High School Exam (Enem) and the Unified Selection System (Sisu) and investigates their relationship with academic performance at the Federal University of Minas Gerais (UFMG). The overall grade point average (GPA) of first and third semester students enrolled at UFMG between 2006 and 2015 were analyzed. The study showed that the two changes in the UFMG´s entrance exam significantly affected the academic performance of students. The first change was the replacement of the first stage of UFMG´s entrance exam by the Enem, only keeping the UFMG´s entrance exam as the second stage. This change is negatively correlated with academic performance, and this correlation remains stable throughout the student’s trajectory at UFMG. The second change was the implementation of Enem/Sisu as the sole stage of the entrance exam, abandoning the second stage of UFMG´s entrance exam. This change had an even stronger negative correlation with the student´s academic performance in the first semester of the course. However, this correlation drops by half when analyzing the third semester, indicating a catching-up of students throughout the course. A downward trend in academic performance was also observed over time, even when the characteristics of the selection process were controlled. These facts were analyzed having as background the expansion of basic and higher education in Brazil, the heterogeneity of Brazilian basic education and the current characteristics of secondary education.